Developer’s Perspective on Implementing a Tool to Facilitate Development of Robotic Process Automation - Vuorela, Sampsa (My University, 2020)
Software robots are programs that can mimic human behavior to interact with other desk- top or web applications used in various business processes. Robotic Process Automation (RPA) is an emerging technology that aims to automate digital processes with software robots. Compared to software development in general, RPA development requires more emphasis on communication between a project’s stakeholders and on the documentation that supports it. Two important pieces of documentation of an RPA project are the Process Design Document (PDD) and the Solution Design Document (SDD). This thesis descri- bes the design and development of a tool that automates the flow of information from a project’s PDD to its SDD. The motivation for this PDD-SDD Tool is to facilitate and streamline the processes included in RPA development. Altogether three rounds of inter- views with practicing RPA developers were conducted to create the first version of the PDD-SDD Tool. The developers were from MOST Digital Ltd, a company specialized in RPA and software robot development. The final interviews indicated the tool to be successful and it will most likely to be developed further to be taken into production use in MOST Digital. The project is based on a background study, conducted jointly with another master’s student Ahmed Abdulghani. The background study is based on scien- tific publications, companies’ white-papers, articles and authors’ work experience. Both this and Abdulghani’s thesis describe this background study, but are otherwise separate pieces of work.
Keywords: robotic process automation, RPA, software development, process flow, code visualization